OP0044 Epidemiology of vasculitis in three regions of europe. (1st June 2001) - Watts, RA; Koldingsnes, W; Nossent, H; Gonzalez-Gay, MA; Garcia-Porrua, C; Bentham, G; Lane, SE; Scott, DG
Abstract : Background: The epidemiology of systemic vasculitis (SV) has been poorly documented. Development of accepted criteria and definitions by the ACR and Chapel Hill Consensus Conference (CHCC) permits comparison of data from different areas. We have reported that Wegener?s granulomatosis (WG) is more common in Norwich (UK) than Lugo (Spain). 1 Objectives: Our aim was to extend our study comparing the epidemiology of WG, microscopic polyangiitis (MPA), polyarteritis nodosa (PAN), Churg Strauss syndrome (CSS) to include a population in the far north of Europe. Methods: Adult patients with a new diagnosis of SV were prospectively identified in Tromsø, North Norway (population 371, 000; latitude 70oN), Norwich (population 420, 000; latitude 52oN), and Lugo, North West Spain (population 241, 000; latitude 43oN) between 1988–98. WG, PAN and CSS were classified using the ACR (1990) criteria and MPA the CHCC definition. 95% confidence intervals (95% CI) were calculated using the Poisson distribution for the observed number of cases. Results: The results are given in the Table 1 . There were 56 patients from Tromso, 86 from Norwich and 41 from Lugo. In all areas and all disease categories the incidence was greater in men than women and peaked aged 65–74 years. Conclusion: We conclude that the overall incidence and pattern of vasculitis in terms of age and sex distribution is similar in the three areas studied. MPA is more common and WG less common in Southern Europe, whilst CSS appears to be more common in Norwich. This study points to the importance of environmental and/or genetic factors in the pathogenesis of vasculitis. Reference: Watts, et al . Ann Rheum Dis. 2001;60:170–2